Femtosaniye Lazer Ablasyonu İle İnce Filmler Üzerinde nano-yapılandırma Ve Karakterizasyon - Şahin, Ramazan (Fen Bilimleri Enstitüsü, 2015)
Bu tez çalışması kapsamında farklı lazer dalgaboyları ve taban açılı aksikonlar kullanılarak metal ince filmler üzerinde fs-lazer Bessel hüzmeleri ile nanometre mertebesinde karmaşık yapılar üretilmiştir. Metal ince filmler üzerinde yapılan optik karakterizasyon (geçirgenlik, yansıma vs. spektrumu ölçümü) yapılarak periyodik yapıların yüzey plazmon modlarını desteklediği gösterilmiştir. Yapılan teorik hesaplamalar, simülasyonlar ve deneyler birbirini doğrulamaktadır. Ayrıca, üretilen yapıların plazmonik tabanlı sensör olarak kullanılabilmesi için gerekli testler yapılmıştır. Grafen tabanlı elektronik uygulamaları genellikle Grafenin yapılandırılmasını gerekmektedir. Grafen optik dalgaboylarında yüksek geçirgenliğe sahip olduğundan lazer ablasyonu esnasında alttaş zarar görebilmektedir. Yapılan optimizasyon deneyleri ile Grafen nano-yapılandırılırken alttaşın neredeyse hiç zarar görmediği SEM, Raman ve sayısal yöntemlerle incelenmiştir. Geliştirilen sayısal yöntemlerle fabrikasyon kalitesi hesaplanarak lazer atım enerjisi ile ilişkilendirilmiştir. Yapılan çalışmalarda % 75 kalite ile grafen üzerinde nm mertebesinde yapıların üretilebileceği gösterilmiştir.

In this work, we exploit the advantageous of non-diffracting Bessel beams to generate nanometer size structures on metal thin films and graphene. We present a detailed study of Bessel beam ablation behavior, using different laser wavelengths and axicon angles. Optical characterization (transmission, reflection) of fabricated structures in the spectral range of 400 nm- 1100 nm shows plasmonic effects. Experimental results are supported by theoretical, numerical and simulations. Near field profiles of fabricated structures clearly show the plasmonic effect. Moreover, shift of the plasmonic resonance is calculated as a function of surrounding medium to investigate the potential of the fabricated structures for sensing. In our experiments we use relatively thin metal films to obtain high signal to noise ratio in transmission. For sensing applications, the relative change in intensity close to the SPR is used for detection. Therefore, this scheme could be effective for plasmonic sensor applications where the low signal-to-noise detection is required. The influence of pulse energy on laser ablation quality and size is experimentally studied on graphene sample. Histogram analysis of fabricated structures gives possibility of quantifying fabrication quality. Graphene based optoelectronic applications require structuring of graphene without any damage to substrate. %75 ablation accuracy is achieved by adjusting beam fluence while keeping the substrate totally intact. Graphene ablation and substrate damage situation are verified through SEM, Raman and numerical methods.
Generation Of Nano-structures On Thin Films through Femtosecond Laser Ablation and Characterization
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (PhD) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: Ablasyon; femtosaniye lazer; grafen; ince film; Ablation; femtosecond laser; graphene; thin film